Development of green concrete using waste marble dust. (2020) - Shukla, Ashish; Gupta, Nakul; Gupta, Ankur
Abstract: The use of industrial waste locks as a raw material to reduce their adverse effects on the environment and to enhance its environmental efficiency. Marble mud powder can be used as a filling assist and leads to can complete voids of concrete construction. This paper shows how to use a 100 percent alternative to natural sand in concrete with the marble mud dust. This research examined the strength of compression and the microstructure of mixed cement. Cement hydration products have been detected by electron microscopy scanning. The strength is described by various parameters: curing time, composition of the binder and (vadium/aggregate) ratio. Composite cements were found at 28 days and higher intensity than 7 days. The greater the strength, the more dust the marble contains. The concrete is thus made of marble dust that contributes to natural resource consumption and to reducing pollution and environmental pollution.